Atorvastatin Induced Proximal Muscle Myopathy-Rare Event of Commonly Used Drug - Sondhi, Sachin; Negi, PC; Sharma, Rajesh; Mahajan, Kunal (Cardiology and Cardiovascular Medicine, 2017)
Statins are commonly used drugs for primary and secondary prevention of coronary artery disease. Statins associated muscle adverse events are not uncommon. Myalgias and myopathy occur with a frequency of 2 to 11 percent.1 However, severe myonecrosis and clinical rhabdomyolysis are much rarer (0.5 percent and less than 0.1 percent, respectively) [1,2]. Statin intolerance was neglected during routine clinical practice. We report a case of 58 year old male who developed severe proximal muscle weakness after giving high dose of atorvastatin.